2022
DOI: 10.1002/ange.202206173
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Oxidative Rearrangement Catalyzed by a Divergent Member of the 2‐Oxoglutarate‐Dependent Dioxygenase Superfamily during Biosynthesis of Dehydrofosmidomycin

Abstract: The biosynthesis of the natural product dehydrofosmidomycin involves an unusual transformation in which 2‐(trimethylamino)ethylphosphonate is rearranged, desaturated and demethylated by the enzyme DfmD, a divergent member of the 2‐oxoglutarate‐dependent dioxygenase superfamily. Although other members of this enzyme family catalyze superficially similar transformations, the combination of all three reactions in a single enzyme has not previously been observed. By characterizing the products of in vitro reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…29 In the context of desaturation reactions between nonactivated carbons, NHFe/α-KG enzymes play a crucial role in breaking two inert C−H bonds. According to the consensus mechanistic models in NHFe/α-KG enzyme desaturation reactions, 6,27,30 three potential pathways have been outlined to depict the removal of the second hydrogen (Scheme 1C). Pathway (a) involves an Fe III −OH intermediate abstracting the second hydrogen, resulting in radical recombination and olefin formation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In the context of desaturation reactions between nonactivated carbons, NHFe/α-KG enzymes play a crucial role in breaking two inert C−H bonds. According to the consensus mechanistic models in NHFe/α-KG enzyme desaturation reactions, 6,27,30 three potential pathways have been outlined to depict the removal of the second hydrogen (Scheme 1C). Pathway (a) involves an Fe III −OH intermediate abstracting the second hydrogen, resulting in radical recombination and olefin formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, recent findings have expanded our understanding as an increasing number of reactions without a lone-pair-bearing α-heteroatom assistance have been reported. These cases include the desaturation reactions catalyzed by PenD in the pentalenolactone biosynthesis (Scheme B), CAS (also known as CS2) in clavaminate biosynthesis, , BcmF in the bicyclomycin biosynthesis, SptF and AndF in meroterpenoids biosynthesis, , DfmD in dehydrofosmidomycin biosythesis, PhrA in berkeleydione biosynthesis, , and AusE in preaustinoid A3 biosynthesis , and the VioC reaction with the non-natural substrate l -homoarginine . Computational studies on VioC, CAS, flavonol synthase, and carbapenem synthase (CarC) , have suggested that the radical recombination proposal [Scheme C, pathway (a)] could also be employed to overcome the barriers.…”
Section: Introductionmentioning
confidence: 99%